Effect of Flame Treatment and Radiofrequency Electromagnetic Radiations on phenolic content in in vitro cultures of Ipomoea batatas - Bag, Urja; Narasimhan, S; Bindu, S (Plant Science Today, 2022)
In vitro grown callus cultures of Ipomoea batatas were exposed to flame treatment and electromagnetic radiations generated by mobile phone. The cultured tissues responded to the treatments as evidenced by the significant reduction of phenolic contents compared to controls. Even though the growth of the tissues was normal, there was a change in the phenolic content of the tissues. There exhibited not much significant variation among the treatments regarding the growth rate. The morphology and texture of the callus also remained the same. It has been concluded that like animal cells, plant cells also respond to non-ionizing radiations like electromagnetic radiation emitted by mobile phones.